2019
DOI: 10.7717/peerj.7821
|View full text |Cite
|
Sign up to set email alerts
|

Integrative transcriptome data mining for identification of core lncRNAs in breast cancer

Abstract: Background Cumulative evidence suggests that long non-coding RNAs (lncRNAs) play an important role in tumorigenesis. This study aims to identify lncRNAs that can serve as new biomarkers for breast cancer diagnosis or screening. Methods First, the linear fitting method was used to identify differentially expressed genes from the breast cancer RNA expression profiles in The Cancer Genome Atlas (TCGA). Next, the diagnostic value of all differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…MAGI2‐AS3 promotes cancer progression through colorectal cancer through regulating miR‐3163/TMEM106B axis (Ren, Li, Tang, Li, & Lang, 2020), whereas in non‐small–cell lung cancer and acute myeloid leukemia, MAGI2‐AS3 inhibits tumor progression by upregulating the expression of the tumor suppressor genes PTEN or LRIG1 (Chen et al, 2020; Hao & Yang, 2019) Therefore, its role in pancreatic cancer is unclear. However, in breast cancer, transcriptome sequencing studies have shown that MAGI2‐AS3 is one of the core tumor suppressor lncRNAs in breast cancer (Zhang et al, 2019), and related mechanism studies have shown that it can promote apoptosis by activating the Fas/FasL signaling pathway and inhibit breast cancer cell proliferation (Y. Yang et al, 2018), MAGI2‐AS3 has the potential to be a diagnostic or prognostic marker for patients with breast cancer. However, the molecular mechanism by which MAGI2‐AS3 inhibits breast cancer remains to be studied, which may provide a new strategy for the diagnosis and treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MAGI2‐AS3 promotes cancer progression through colorectal cancer through regulating miR‐3163/TMEM106B axis (Ren, Li, Tang, Li, & Lang, 2020), whereas in non‐small–cell lung cancer and acute myeloid leukemia, MAGI2‐AS3 inhibits tumor progression by upregulating the expression of the tumor suppressor genes PTEN or LRIG1 (Chen et al, 2020; Hao & Yang, 2019) Therefore, its role in pancreatic cancer is unclear. However, in breast cancer, transcriptome sequencing studies have shown that MAGI2‐AS3 is one of the core tumor suppressor lncRNAs in breast cancer (Zhang et al, 2019), and related mechanism studies have shown that it can promote apoptosis by activating the Fas/FasL signaling pathway and inhibit breast cancer cell proliferation (Y. Yang et al, 2018), MAGI2‐AS3 has the potential to be a diagnostic or prognostic marker for patients with breast cancer. However, the molecular mechanism by which MAGI2‐AS3 inhibits breast cancer remains to be studied, which may provide a new strategy for the diagnosis and treatment of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatics analysis of prognostic biomarkers for human bladder cancer (22) showed that MAGI2-AS3 was downregulated in bladder cancer samples, and it was identi ed as the hub lncRNA in the ceRNA network. The tumor-suppressive role of MAGI2-AS3 has also been con rmed in multiple studies related to breast cancer (23)(24)(25). In a study on hepatocellular carcinoma (HCC) (26), the tumor-suppressive role of MAGI2-AS3 and targeted regulatory relationship between MAGI2-AS3 and miR-374b-5p were also con rmed.…”
Section: Discussionmentioning
confidence: 83%
“…Then, the soft threshold is calculated by WGCNA algorithm. The scale-independent value and average connectivity of modules under different soft thresholds were tested by the gradient method in order to determine the appropriate soft threshold [13, 16, 17]. By selecting appropriate soft threshold values, the co-expression network was constructed to ensure the authenticity of the results, and the minimum number of genes in each module was not <30.…”
Section: Methodsmentioning
confidence: 99%